Pharmacologic Activation of Angiotensin-Converting Enzyme II Alleviates Diabetic Cardiomyopathy in db/db Mice by Reducing Reactive Oxidative Stress - Donghyun Kim; Wooju Jeong; Yumin Kim; Jibeom Lee; Sung Woo Cho; Chang-Myung Oh; Raekil Park (Diabetes & Metabolism Journal, 2023)
Background Diabetes mellitus is one of the most common chronic diseases worldwide, and cardiovascular disease is the leading cause of morbidity and mortality in diabetic patients. Diabetic cardiomyopathy (DCM) is a phenomenon characterized by a deterioration in cardiac function and structure, independent of vascular complications. Among many possible causes, the renin-angiotensin-aldosterone system and angiotensin II have been proposed as major drivers of DCM development. In the current study, we aimed to investigate the effects of pharmacological activation of angiotensin-converting enzyme 2 (ACE2) on DCM. Methods The ACE2 activator diminazene aceturate (DIZE) was administered intraperitoneally to male db/db mice (8 weeks old) for 8 weeks. Transthoracic echocardiography was used to assess cardiac mass and function in mice. Cardiac structure and fibrotic changes were examined using histology and immunohistochemistry. Gene and protein expression levels were examined using quantitative reverse transcription polymerase chain reaction and Western blotting, respectively. Additionally, RNA sequencing was performed to investigate the underlying mechanisms of the effects of DIZE and identify novel potential therapeutic targets for DCM. Results Echocardiography revealed that in DCM, the administration of DIZE significantly improved cardiac function as well as reduced cardiac hypertrophy and fibrosis. Transcriptome analysis revealed that DIZE treatment suppresses oxidative stress and several pathways related to cardiac hypertrophy. Conclusion DIZE prevented the diabetes mellitus-mediated structural and functional deterioration of mouse hearts. Our findings suggest that the pharmacological activation of ACE2 could be a novel treatment strategy for DCM.